Effect of ball inclusion on jump performance in soccer players: a biomechanical approach - Filter, A.; Jabalera, J. O.; Molina-Molina, A.; Suarez-Arrones, L.; Robles-Rodríguez, J.; Dos`Santos, T.; Loturco, I.; Requena, B.; Santalla, A. (Science and Medicine in Football, 2022)
Objective: In soccer, vertical jump means jumping toward a ball. Since no vertical jump test includes the ball as a reference element, the effect that the ball would have in a vertical jump test is unknown. The aim of this study was to examine the biomechanical differences between run-up vertical jump measurements without (Run-up Vertical Jump) and with ball inclusion (Heading Test).